Empathy and its correlation to Job Satisfaction A field study on a sample of kindergarten female teachers in Lattakia province - الشريف . ليلى; علي وفيقة; سعيد غيداء (Latakia University Journal - Arts and Humanities Sciences Series, 2021)
This search aimed to study the correlation between empathy and job satisfaction, and the differences in empathy and job satisfaction according to (year of experiences) variable. A sample of (60) kindergarten female teachers was assigned randomly from private kindergartens in Lattakia city. The scales of empathy prepared by Steckal (1994) translated by the researcher, and job satisfaction prepared by Hibah (2016) were used. The researcher followed the descriptive analytical curriculum. The results indicated that there is a moderate level of empathy and job satisfaction among kindergarten female teachers, a positive significant correlation between empathy and job satisfaction, and statistically significant differences in empathy and job satisfaction according to (years of experience) variable.